Analysis of Factors Affecting Clinical Learning of Midwifery Students - Habibah, Minda; Susanti, Ari Indra (Universitas Gadjah Mada, 2024)
Background: Clinical learning plays an important role in midwifery education because students can apply theoretical knowledge to real-life practice. Effective clinical learning can enhance students' practical skills, critical thinking, and self-confidence, while also offering direct learning experiences with clients. This is important in building students' clinical competence to support their careers as midwives.Aims: This study aims to analyze the factors that influence the clinical learning of midwifery students and to understand how these factors impact the learning process. Methods: A scoping review was conducted in this study. The articles used were those published in the last five years, from 2019 to 2024, following the inclusion and exclusion criteria, which resulted in13 articles. Results: The scoping review's findings revealed that student characteristics, practice areas, guidance, and supervision, as well as learning and assessment methods, had a significant impact on the effectiveness of midwifery students' clinical learning. Conclusion: Fostering good relationships among educational institutions, preceptors, and midwifery students is very important for achieving clinical learning objectives.Innovation in clinical learning is needed to enhance the competencies of midwifery students.